Distinct patterns of parental involvement in Chinese families and preschoolers’ social adjustment - Wu, Zhongling; Zhang, Dianyue; Chen, Lichun; Chen, Liang; Zhang, Wenxin (Frontiers in Psychology, 2025)
IntroductionParental involvement during early childhood is crucial for promoting children’s social development. However, few studies have explored both maternal and paternal involvement and their combined effects on children’s social adjustment.MethodsThe person-centered approach was conducted to examine the profiles of maternal and paternal involvement in a sample of 535 Chinese families with preschool children. Furthermore, the present study investigated the associations between these parental involvement profiles and preschoolers’ social adjustment.Results and conclusionLatent profile analysis identified a total of four profiles of parental involvement: Moderate maternal-low paternal involvement profile (21.9%), Both moderate involvement profile (38.1%), High maternal-moderate paternal involvement profile (28.2%), and Both high involvement profile (11.8%). Children in Both high involvement and High maternal-moderate paternal involvement profiles exhibited higher social skills compared to those in lower-involvement profiles. These findings enhance our understanding of home-based parental involvement patterns and their associations with preschoolers’ social development.